Preliminary Anticancer Potency Evaluation and Phytochemical investigation of Methanol Extract of Piper claussenianum (Miq.) C. DC. - André M. Marques, Renan A. de Paiva, Leonardo M. da Fonseca, Marcia A. M. Capella, Elsie F. Guimarães and Maria Auxiliadora C. Kaplan (Journal of Applied Pharmaceutical Science, 2013)
Bioassay guided isolation of active natural compounds was performed to investigate the anti-tumor potential of the crude extract and isolated compounds from inflorescences of Piper claussenianum. LC-DAD-UV, GC-MS and NMR analyzes revealed the presence of phenolic metabolites in the methanol crude extract. Phytochemical procedures lead to the isolation of the major flavonoids, 2’,6’-dihydroxy-4-methoxychalcone, 5,7-dihydroxyflavanone and 5-methoxy-7-hydroxyflavanone that were assayed for inhibition or viability stimulation of the human breast cancer cell line MCF-7. The results suggest the 2’,6’-dihydroxy-4-methoxychalcone as the biologically active compound in the crude methanol extract of inflorescences from P. claussenianum. The crude extract was found as potential natural source of compounds with breast cancer cell inhibition properties. All isolated compounds have not been described from this species yet.
Keywords: Piperaceae, Piper claussenianum